Exemplary of post graduate programs in the Department of Arabic Language and Literature: aspirations and constraints = برنامج الدراسات العليا المتميز في قسم اللغة العربية وآدابها: تجربة بين الطموحات والمعوقات - Hj. Yaakub, Muhamadul Bakir; Uwais, Nor Syarif (2013)
Post Graduate Program is an important element of Higher Learning Institution